Coexistence of immune thrombocytopenic purpura and alopecia areata: Possible relationship - Kose, Dogan; Solmaz, Abdullah; Guzelcicek, Ahmet; Aslan, Halil (Annals of Medical Research, 2021)
None
Keywords: Alopecia areata; immune thrombocytopenia; purpura; childhood